Performance analysis of a hydraulic tidal turbine for seawater desalination (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Tidal energy is increasingly recognized as a viable renewable energy source with applications extending beyond electricity generation, including seawater desalination for coastal and off-grid communities. This study investigates a novel direct-driven tidal desalination system that eliminates intermediate electrical conversion by mechanically coupling a horizontal-axis tidal turbine to a high-pressure positive displacement pump and a Seawater Reverse Osmosis system with an integrated energy recovery device. The system converts the mechanical power of the turbine into hydraulic energy, driving pressurized seawater through reverse osmosis membranes to produce freshwater, while the brine is recirculated through the Energy Recovery Device to improve efficiency. A time-domain numerical model simulates the system's performance in the below-rated, variable-speed operational range for two configurations under steady-state and turbulent tidal flow conditions.Results indicate that the proposed variable displacement configuration maintains a constant tip speed ratio and offers more stable operation. A 140 kW rotor is capable of producing up to 88.3 m3/h of freshwater at rated current speed, with a specific energy consumption of 3.2 kWh/m3.  Under turbulent flow, it achieved an 8% increase in freshwater production with respect to the fixed pumped configuration, as well as lower pressure fluctuations while maintaining a constant recovery rate. These findings suggest that active hydraulic control enhances the efficiency, stability, and freshwater output of direct-driven tidal desalination systems. However, practical constraints such as membrane flow limits, cavitation risk, and rotor fatigue at high speeds must be addressed in future design considerations.This work highlights the potential and challenges of integrating tidal energy directly into desalination processes and provides insights into system optimization under realistic operating conditions.